2006
DOI: 10.1021/bi060999o
|View full text |Cite
|
Sign up to set email alerts
|

The Plasticins:  Membrane Adsorption, Lipid Disorders, and Biological Activity

Abstract: The present study investigates the relationships between structural polymorphism, adsorption onto membrane mimetic support, lipid disturbance, and biological activity of bactericidal 23-residue, glycine-leucine-rich dermaseptin orthologues from the Phyllomedusinae frog skin, the "plasticins". Biological activities were evaluated using the membrane models DMPG (1,2-dimyristoyl-sn-glycero-3-phosphatidylglycerol) for prokaryotic membranes and DMPC (1,2-dimyristoyl-sn-glycero-3-phosphatidylcholine) for eukaryotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 39 publications
2
47
0
1
Order By: Relevance
“…This distance was 30-35 Å for a-helical structure and 70-80 Å for a totally extended structure. 1,3 In Figure 6A,CaG1-CaG23 distances compatible with b-hairpin conformations are those for PD36 and PD36KF. They underwent transitions between three conformations (helix/coil/b-hairpin shaped structure) with different coil transition states, more extended for PD36 (CaG1-CaG23 & 40 Å ) than PD36KF (CaG1-CaG23 & 15-20 Å ).…”
Section: Structural Malleability Of Plasticins 49mentioning
confidence: 98%
See 4 more Smart Citations
“…This distance was 30-35 Å for a-helical structure and 70-80 Å for a totally extended structure. 1,3 In Figure 6A,CaG1-CaG23 distances compatible with b-hairpin conformations are those for PD36 and PD36KF. They underwent transitions between three conformations (helix/coil/b-hairpin shaped structure) with different coil transition states, more extended for PD36 (CaG1-CaG23 & 40 Å ) than PD36KF (CaG1-CaG23 & 15-20 Å ).…”
Section: Structural Malleability Of Plasticins 49mentioning
confidence: 98%
“…In previous papers, we have shown that the presence of K8, K12 lysines were determinant for antimicrobial activity. 1,3 So, the contribution of these residues was investigated within PD36 series: PD36, two virtual mutants (PD36K 8, PD36K 12 ) and the analogous PD36K 8 K 12 . Figure 7 pointed out the large conformational behavior splitting for the studied series.…”
Section: Structural Malleability Of Plasticins 49mentioning
confidence: 99%
See 3 more Smart Citations